Examining the Sustainable Development Goals: Key Insights and Practical Strategies for Implementation - Sharma, Lok Raj; K. C., Abhishek; Sharma, Sumisha; Sharma, Sushant (International Research Journal of MMC, 2026)
The Sustainable Development Goals (SDGs) provide a comprehensive global framework for promoting inclusive socio-economic development, environmental sustainability, and institutional resilience, yet their effective implementation remains a significant challenge across diverse national and local contexts. This study adopted a qualitative exploratory research design in which secondary data were collected from relevant books, scholarly articles, and credible website documents. This study aims to examine the Sustainable Development Goals and to suggest practical strategies for their implementation. Qualitative secondary data were analyzed using critical analysis. The study examines all 17 Sustainable Development Goals and identifies the strategic pathways for their implementation. The analysis reveals that although the SDGs provide a comprehensive framework for sustainable development, their implementation is hindered by governance gaps, financial constraints, institutional weaknesses, and structural inequalities. Effective implementation requires integrated policies, inclusive governance, community participation, strategic partnerships, and strengthened institutional capacity. The findings provide useful insights for students, educators, academic institutions, policymakers, and local communities seeking to strengthen SDG implementation through education, capacity building, and collaborative action.